Influence of the course of electrostimulation by the device "VEB-1" on parameters of electroencephalogramm at practically healthy males - Babelyuk, Valeriy Ye; Babelyuk, Nazariy V; Popovych, Igor L; Dobrovol’s’kyi, Yuriy G; Korsuns’kyi, Igor H; Korolyshyn, Tetyana A; Kindzer, Bohdan M; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Background. We created and patented device for electrostimulation "VEB-1". It is intended for activation of functional systems of organism by wave influence on nerve plexus by frequency beats method.This article launches a series of articles on the influence of this device on the parameters of the neuroendocrine-immune complex and the metabolism of various categories of people. Materials and Methods. The object of observationwere 14 males aged 24-59 years without clinical diagnose but with dysfunction of neuro-endocrine-immune complex and metabolism. In the basal conditions we recorded electroencephalogram(EEG) a hardware-software complex “NeuroComStandard” (KhAIMedica, Kharkiv, Ukraine). Then the volunteers were subjected to an electrostimulation session lasted for 21 minutes in four days. One day after the last session, the EEG was re-registered. Results. 20 parameters of EEG were identified, in which the volunteers’ neurodynamics before and after the course of electrostimulation differed considerably (Squared Mahalanobis Distance make up 191; F=16,7; p<10-3). The neurotropic stimulation effect has a modulating character, namely: the initially decreased spectral power density (SPD) of the alpha-rhythm in F3, F4, T4, T5 loci as well as of theta-rhythm in P3 locus increases; decreased SPD of beta-rhythm in the F3, C3, C4, P3, P4 and O2 loci as well as Amplitude of beta-rhythm becomes even smaller; the initially increased SPD of delta-rhythm in the loci Fp1, F8 and P4 rises further. Conclusion. A four-day electrostimulation course causes on males with dysfunction of the neuro-endocrine-immune complex and metabolism a notable neuro-modulating effect evaluated by changes in basal EEG.